Air Transport and Connectivity: Evidences on the Emergence of Tourist Nucleuses in the World Urban System - Gago-García, Cándida; Díez-Pisonero, Roberto; Córdoba-Ordóñez, Juan (Revista de Estudios Andaluces, 2019)
Air transportation and tourism are undoubtedly two of the main vectors on globalization processes with a deep interrelation between them. The research deeps on these relationships at measuring the changes on the top 100 touristic city ranking (2006- 2016). The air transportation indicators, such as the total number of flights, facilitates to interpret the results. In the end, the analysis shows the way and the scope of the irruption of touristic nuclei in the world urban system and what is their international meaning. Some of these cities are global ones, with a huge range of activities and functions but the emergence of another type of touristic cities is due to their specific functional roles. The result depicted the rise of very important nuclei, mainly in the Asia-Pacific region and at the same time, the rearrangement of functional weights and meanings of the great world tourist regions